Software Complexity and Organization of Firms’ Offshoring Activities - Arto Ojala; Eriikka Paavilainen-Mäntymäki; Ning Su; Kalle Lyytinen (My University, 2022)
How does software complexity shape software providers' offshoring tasks, and how
do such firms organize their offshoring activity? These questions are important, since the
global software development market is growing rapidly, offering new opportunities for
software managers and entrepreneurs to distribute their activities geographically. Based on
a multi-site case study of 12 software firms, we study connections between software
complexity and the offshoring strategies selected. Our findings suggest that software firms
select a variety of organizational structures for their offshoring activity, and that the selection
is shaped by the complexity of the software in question.
Nordic Contributions in IS Research: 8th Scandinavian Conference on Information Systems, SCIS 2017, Halden, Norway, August 6-8, 2017, Proceedings